2012
DOI: 10.1186/1471-2377-12-11
|View full text |Cite
|
Sign up to set email alerts
|

Meningeal and cortical grey matter pathology in multiple sclerosis

Abstract: Although historically considered a disease primarily affecting the white matter of the central nervous system, recent pathological and imaging studies have established that cortical demyelination is common in multiple sclerosis and more extensive than previously appreciated. Subpial, intracortical and leukocortical lesions are the three cortical lesion types described in the cerebral and cerebellar cortices of patients with multiple sclerosis. Cortical demyelination may be the pathological substrate of progres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
149
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 173 publications
(167 citation statements)
references
References 53 publications
(115 reference statements)
6
149
3
Order By: Relevance
“…7,8,11 Studies in patients with RRMS showed that GM atrophy is a meaningful indicator of neurodegeneration and occurs more rapidly than WM atrophy during both the early and advanced stages of MS. [4][5][6]12 Moreover, GM atrophy is a better indicator of disability progression than WM atrophy or accumulation of lesion burden. [4][5][6]13 Cognitive impairment in patients with RRMS is thought to be associated with MS-related GM pathology, particularly in the cortex, 14 with variability in disability progression among patients with RRMS possibly arising from differences in GM injury.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…7,8,11 Studies in patients with RRMS showed that GM atrophy is a meaningful indicator of neurodegeneration and occurs more rapidly than WM atrophy during both the early and advanced stages of MS. [4][5][6]12 Moreover, GM atrophy is a better indicator of disability progression than WM atrophy or accumulation of lesion burden. [4][5][6]13 Cognitive impairment in patients with RRMS is thought to be associated with MS-related GM pathology, particularly in the cortex, 14 with variability in disability progression among patients with RRMS possibly arising from differences in GM injury.…”
mentioning
confidence: 99%
“…15 It is likely that GM pathology reflects increased cortical and SDGM damage and atrophy, which may also underlie other aspects of MS-associated disability. [1][2][3]7,8 Several case-control studies have established that SDGM but not cortical atrophy is present at the earliest clinical stages of the disease. [16][17][18][19][20] Other studies indicate that damage to the SDGM is associated with memory impairment.…”
mentioning
confidence: 99%
“…It appears, therefore, that as the disease evolves into the progressive stage, the inflammation becomes compartmentalized and predominantly mediated by B cells. Such "slow" in situ inflammation can be detected even in the cortex and the deep grey matter and seems to correlate with the progression of disability [33,[35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50].…”
Section: Discussionmentioning
confidence: 99%
“…Although MS has traditionally been considered a disease of the white matter, there is an increasing body of evidence that gray matter is involved by the pathological process since the early stage of the disease and has a significant impact on physical and cognitive disability. 55 Conversely, although classic neurodegenerative diseases are thought to be characterized by a selective and localized damage of GM, advanced quantitative MRI techniques can demonstrate a diffuse involvement of WM. 56 (TSPO), 51 a protein that is upregulated in activated microglia.…”
Section: Imaging Techniques To Detect and Monitor Neurodegenerationmentioning
confidence: 99%
“…This is in part supported by MRI studies showing a certain degree of correlation between WM injury and cortical atrophy. [57][58][59] However, a number of MRI studies 55 have demonstrated that GM pathology (both cortical lesions and atrophy) is already evident at the earliest stages of the disease when the WM lesion load is quite modest 60 suggesting that GM could be the primary target of the disease process, resulting in secondary axonal degeneration and demyelination of WM. 62 and become more prominent as the disease progresses.…”
mentioning
confidence: 99%